In search of a new perspective: Cross-linguistic influence in the acquisition of third language phonology - Wrembel, Magdalena (Wydawnictwo Naukowe UAM, 2015)
The books explores the phenomenon of cross-linguistic influence (CLI) in phonological acquisition from a multilingual perspective. A distinction is made between second vs. third language acquisition and the complexity of the latter process as well as its conditioning factors are elaborated on. The contribution aims to test the tenets of the current theoretical models of multilingual acquisition including the L2 Status Model, the Cumulative Enhancement Model and the Typological Primacy Model. To this end, three studies were conducted in parallel on four groups of participants with varying language combinations (i.e. mirrored L2 and L3 sets). The studies involved (1) accentedness, comprehensibility and accuracy ratings assessing the perceived phonetic performance in the L3, (2) acoustic measurements of voice onset time (VOT) in the L1, L2 and L3 as a correlate of foreign accentedness, and (3) the degree of metaphonological awareness generated from oral protocols. The results were analysed separately for each study as well as globally by means of across groups and across studies comparisons. The findings indicate that CLI in the L3 phonological acquisition may have multiple sources including both the native and non-native languages, that it's gradual and structure dependent and that the proposed models can account only partially for its specificity.
Keywords: third language (L3); phonological acquisition; cross-linguistic influence